Usability testing of an e-learning resource designed to improve medical students' physical activity prescription skills: a qualitative think-aloud study. Issue 7 (6th July 2021) - Carter-Roberts, Helen; Antbring, Richard; Angioi, Manuela; Pugh, Gemma
Abstract : Objective: An e-learning resource (MEdic GAming, MEGA) was developed based on the contents of the Faculty of Sports and Exercise Medicine exercise prescription booklet. This study aimed to (i) explore medical students' perspectives of physical activity promotion and e-learning and (ii) investigate medical students' response to the design, content and usability of the MEGA e-learning resource. Design: Qualitative think-aloud interview study. Setting: A London medical school. Participants: 19 undergraduate medical students were interviewed using the think-aloud method while using the e-learning resource concurrently. Results: In general, medical students felt current education on physical activity is inadequate and held a strong desire for more teaching on exercise medicine. Students believed the MEGA e-learning resource addressed a gap in their knowledge on physical activity but noted e-learning should not replace face-to-face teaching and suggested physical activity education would be best delivered through a blended learning approach. Students felt such an approach would allow better opportunity to practice physical activity counselling skills with patients while on clinical placement. Students' motivation to engage with the MEGA e-learning resource was positively impacted by aesthetically appealing design and interactive gamification elements such as self-assessment quizzes and visual progress tracking. Conclusion: Medical students value the role of physical activity in health but are disappointed by the lack of teaching within the current medical curriculum. E-learning resources, such as MEGA, which contain interactive features are a viable means to integrate physical activity into the undergraduate curriculum but should be supplemented by the opportunity to practice physical activity counselling in-person.